Eighteen‐month lamivudine prophylaxis on preventing occult hepatitis B virus infection reactivation in patients with haematological malignancies receiving immunosuppression therapy. Issue 2 (29th November 2017) - Marrone, A.; Capoluongo, N.; D'Amore, C.; Pisaturo, M.; Esposito, M.; Guastafierro, S.; Siniscalchi, I.; Macera, M.; Boemio, A.; Onorato, L.; Rinaldi, L.; Minichini, C.; et al.
Summary: This study evaluated the long‐term efficacy and safety of an 18‐month lamivudine prophylaxis in 68 HBsAg‐negative/anti–HBc‐positive patients with oncohaematological disease. All 68 consecutive HBsAg‐negative/anti–HBc‐positive patients with an oncohaematological disease and naïve for chemotherapy observed from April 2008 to December 2012 at 2 Hematology Units in Naples were treated with lamivudine for 18 months after stopping chemotherapy and monitored for HBsAg at months 1 and 3 during chemotherapy and then every 3 months after its discontinuation. During follow‐up, 13 (19.1%) of the 68 patients died of complications related to their oncohaematological disease, and 3 (4%) showed a virological HBV reactivation (retroconversion to HBsAg positivity) 1‐7 months after the discontinuation of lamivudine prophylaxis (2 treated for chronic lymphocytic leukaemia and one for Waldenstrom's disease); of these, 2 showed a biochemical reactivation. Comparing the demographic and clinical characteristics of the 3 patients with a virological HBV reactivation to the 65 without, the former were older (median age and range: 67 years [75‐78] vs. 61 [24‐88]; P = .05) and were less frequently treated for B‐cell non‐Hodgkin lymphoma (B‐NHL) (0 vs. 70.7%, P = .03). In conclusion, a 18 months of lamivudine prophylaxis was effective in preventing HBV reactivation in HBsAg‐negative/anti–HBc‐positive patients treated for B‐NHL. However, in patients with chronic and severe immunodepression, such as those with chronic lymphocytic leukaemia and Waldenstrom's disease, prophylaxis should be continued for an indefinite period.